Ink on Paper: A Study of Line Quality and Fluid Dynamics in Handwritten Documents - Rudrank, Shukla; Janaki, M C (Journal of Neonatal Surgery, 2025)
Handwriting and document analysis is a major area of forensic science. The present research attempts to study the line quality of handwritten documents, which is useful for comparing and analyzing questioned documents. This study examines the differences in line quality produced by 0.5mm ballpoint pens, commonly used in daily life. The objective is to determine whether any differences exist between different pens of the same tip caliber. For this study, a stereomicroscope was used to capture images of handwritten documents collected by the researcher. Specialized software was then used to measure line quality. The results indicate that even when using pens of the same caliber, the line quality varied depending on the pen. This variation was observed not only in standard writing but also in scribbling motions such as vertical and horizontal strokes, where differences in line quality were also evident. Furthermore, the study applied Fick’s time-dependent diffusion law of fluid dynamics to determine the age of ink. Combining line quality data with Fick’s law of diffusion provided valuable insights. It was found that handwriting produced with pens of the same caliber exhibited disparities, and if such writing was added at a later time, diffusion analysis could help detect alterations or additions to the original writing. These findings highlight the practical application of fluid dynamics laws in handwriting analysis and the detection of alterations in questioned documents.